Coping with stereotype threat: Multiple identities and the role of gender-professional identity integration (G-PII) - LIM, Amy Jia Ying (Institutional Knowledge at Singapore Management University, 2018)
Negative stereotypes concerning females’ inferior quantitative abilities continue to hinder females’ preference and success in science, technology, engineering, and mathematics (STEM) fields. Studies on multiple identities show that priming females with a favorable identity, a social identity they possess that is associated with superior quantitative abilities, can reduce the aversive effects of stereotype threat. However, this line of research overlooked the fact that females manage their multiple identities in different ways and therefore respond to identity cues differently. This paper examined the role of gender-professional identity integration (G-PII), an individual difference on perceived compatibility of gender and professional identities, in influencing how women cope with stereotype threat when a favorable identity is primed. Study 1 examined how female professionals with varying levels of G-PII react to identity cues differently. Results show that only Low G-PIIs were sensitive to the identity cues and behaved in accordance to the primed identity. In contrast, High G-PIIs were not significantly influenced by the identity cues. Moreover, performance differences were only observed in a domain where females are stereotyped against (i.e., in a math test). Study 2 investigated how G-PII influences the effects of stereotype threat when a favorable identity is made salient during stereotype threat and the underlying mechanism that accounts for the performance difference observed amongst females with different levels of identity integration. The findings of Study 2 were not significant but were consistent with the prediction that Low G-PIIs spend more cognitive effort in processing identity cues, depleting those that could have been use for subsequent performance task. The theoretical implications, practical implications, and future directions of this paper will then be discussed.